Cluster-randomised controlled trials of individual and combined water, sanitation, hygiene and nutritional interventions in rural Bangladesh and Kenya: the WASH benefits study design and rationale - F. Arnold, Benjamin; Null, Clair; P. Luby, Stephen; Unicomb, Leanne; Ahmed, Tahmeed; Ashraf, Sania; Christensen, Garret; Clasen, Thomas; Dentz, Holly N.; Fernald, Lia C H; Haque, Rashidul; Hubbard, Alan E.; et al. (© 2013 BMJ Open, 2017)
This article was published in the BMJ Open [© 2013 BMJ Open] and The Journal's website is at: http://bmjopen.bmj.com/content/3/8/e003476